O Letramento feminista na educação linguística crítica: uma experiência com professoras/es de línguas formação - (:unkn) unknown (Universidade Estadual de Goiás, 2024)
I set out to explore feminist literacy as a powerful tool for fostering critical thinking in language teacher education. Through the creation and facilitation of a short course on this topic, I aimed not only to share knowledge but also to understand how participants perceived and interpreted their experience of feminist teacher education. Additionally, I sought to uncover the possibilities for language teaching informed by the feminist literacies that emerged during the process. This work is rooted in the belief that feminist education is essential for promoting critical, socially just approaches to teaching. The study focused on the journey of five undergraduate students from Language programs across different Brazilian universities. To support this exploration, I drew on theoretical insights from Jordão (2013), Monte Mór (2013), Duboc (2014), Freire (2005), Silvestre (2017, 2018), Sabota (2018), Sardinha (2018), Hooks (2017), Cadilhe (2020), and Souza (2011), who connect education and critical literacies to the development of reflective thinking and transformative actions. The feminist dimension of the study was informed by the works of Hooks (2017, 2020), Vergés (2020), Collins and Bilge (2021), and González (2020), alongside other authors who have advanced feminist theory and emphasized the need for inclusive feminist education. To capture the participants' perspectives, I used a variety of empirical materials, including initial narratives,discussions during synchronous meetings, collaborative curations on Padlets, and final narratives. Analyzing these materials revealed that the short course effectively supported the construction of a feminist approach to teacher education. Ultimately, this research highlights the pressing need for academic spaces that encourage the development of feminist praxis, fostering educators who are prepared to address social inequities through critical and compassionate teaching.
Feminist literacy within critical language education: a study with pre-service language teachers
Keywords: Letramento Feminista; Educação Linguística Crítica - Formação de professores; Feminist Literacy; Critical Language Education - Teacher Education; CIENCIAS HUMANAS::EDUCACAO; LINGUISTICA::TEORIA E ANALISE LINGUISTICA